Syn and anti conformers of diammonium aquabis(malonato)oxidovanadate(IV) in an anhydrate crystal - Keiji Ohno; Takumi Yoshida; Akira Nagasawa; Takashi Fujihara (Acta Crystallographica Section E: Crystallographic Communications, 2018)
The asymmetric unit of the title anhydrate compound, (NH4)2[VO(C3H2O4)2(H2O)], consists of two independent complex anions and four ammonium cations. In the complex anions, the VIV atoms are each coordinated by two malonate ligands, one water molecule and one oxide O atom in a distorted octahedral geometry. The equatorial plane is formed by the malonate O atoms, while the axial positions are occupied by water and oxide O atoms. The difference between the two independent complexes is the relative conformation of the malonate ligands. The two ligands in one complex anion are in a syn conformation, while in the other they adopt an anti conformation. In the crystal, the complex anions interact with the counter-cations and adjacent anions through O—H...O, N—H...O and C—H...O hydrogen bonds. Stacks of alternating layers consisting of either anti or syn isomers, formed with the aid of the hydrogen bonding, are observed. DFT calculations for the anti and syn isomers show a similar thermodynamic stability to each other. The crystal used for this analysis was an inversion twin with the ratio of the twin components being 0.270 (13):0.730 (13).